2015
DOI: 10.1007/s00359-015-0995-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative histology of the adult electric organ among four species of the genus Campylomormyrus (Teleostei: Mormyridae)

Abstract: The electric organ (EO) of weakly electric mormyrids consists of flat, disk-shaped electrocytes with distinct anterior and posterior faces. There are multiple species-characteristic patterns in the geometry of the electrocytes and their innervation. To further correlate electric organ discharge (EOD) with EO anatomy, we examined four species of the mormyrid genus Campylomormyrus possessing clearly distinct EODs. In C. compressirostris, C. numenius, and C. tshokwe, all of which display biphasic EODs, the poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…6). A previous 490 study demonstrated that EOD duration changes substantially with growth in C. numenius, and 491 this correlates with ontogenetic changes in EO anatomy (Paul et al, 2015). For many mormyrid 492 species, EOD waveform varies with ontogeny, sex, relative dominance, and season (Bass, 1986;493 Hopkins, 1999;Carlson et al, 2000;Werneyer and Kramer, 2006).…”
Section: Courses 465mentioning
confidence: 96%
See 1 more Smart Citation
“…6). A previous 490 study demonstrated that EOD duration changes substantially with growth in C. numenius, and 491 this correlates with ontogenetic changes in EO anatomy (Paul et al, 2015). For many mormyrid 492 species, EOD waveform varies with ontogeny, sex, relative dominance, and season (Bass, 1986;493 Hopkins, 1999;Carlson et al, 2000;Werneyer and Kramer, 2006).…”
Section: Courses 465mentioning
confidence: 96%
“…We grouped EODs of C. numenius into three arbitrary types based on variation in 149 duration (Long, Intermediate, and Short EOD), following a previous study that revealed 150 extensive individual variation in EOD duration within this species (Paul et al, 2015). In the 151 following analysis, we used the average value without separating types.…”
Section: Introduction 68mentioning
confidence: 99%
“…Mormyrids evolved an electric organ enabling them to produce electric organ discharges (EODs) for orientation and communication, i.e., mate recognition and species discrimination [9][10][11][12][13][14]. The main structure of electric organs is formed by tens of specialized cells, called electrocytes, which have a disk-like shape and are stacked in cylindrical columns [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Either the anterior or the posterior face of electrocytes gives rise to several finger-like evaginations fusing in a stalk, serving as the interface to the electromotor neuron. Those stalks can penetrate the electrocyte and occur as single-or multiple stalk-systems [15][16][17][18]. The electrocyte faces can be smooth or unevenly invaginated with papillae or folds increasing the membrane's surface [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation